Survival, Resistance, and the Canadian State: The Transformation of New Brunswick’s Native Economy, 1867-1930 - Parenteau, Bill; Kenny, James (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2002)
AbstractBetween Confederation and 1930, the economic life of the Mi'kmaq and Maliseet First Nations of New Brunswick underwent a broad transformation, as hunting, fishing and trapping were progressively supplanted by agriculture, the production of handicrafts and, especially, wage labour. The First Nations of the province experienced this transformation as a dual struggle of survival and resistance. They may have integrated, mostly out of necessity, into the larger provincial economy, but they also persisted in long-established patterns of fish and game harvesting, often in defiance of federal and provincial regulations. Moreover, the maintenance of hunting, fishing, and trapping as important economic activities was underscored by a consistent assertion that Native rights to the forest, fish, and game resources of the province were vested in treaties negotiated with British colonial authorities.